Peranan Pondok Pesantren Al-Ittifaq dalam Bidang Agribisnis terhadap Kehidupan Masyarakat Alamendah Bandung 1970-1998 - Arislan, Andika Dwiki; Zakaria, Mumuh Muhsin; Falah, Miftahul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Al-Ittifaq Islamic boarding school is an educational institution that integrates religious education with social life, and it differs from other boarding schools because it also focuses on agribusiness. The agribusiness activities began due to the boarding school’s need to support all the students and staff living there. This study aims to uncover the establishment and development of Al-Ittifaq Islamic boarding school in the field of agribusiness, and to explore its role in the lives of the students and the community in Ciburial, Alamendah Village, Rancabali District in the agribusiness sector. The research method used is oral history, which involves four stages: heuristics, criticism, interpretation, and historiography. Data collection techniques include participatory observation and in-depth interviews. The results of this study show that Al-Ittifaq Islamic boarding school was founded in 1934 by K.H. Mansyur. In 1980, agribusiness activities impacted both the students and the surrounding community, benefiting both parties.